2019
DOI: 10.3390/ijms20246339
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profile of Oviductal Extracellular Vesicles across the Estrous Cycle in Cattle

Abstract: Oviductal extracellular vesicles (oEVs) have been proposed as key modulators of gamete/embryo maternal interactions. The aim of this study was to examine the metabolite content of oEVs and its regulation across the estrous cycle in cattle. Oviductal EVs were isolated from bovine oviducts ipsilateral and contralateral to ovulation at four stages of the estrous cycle (post-ovulatory stage, early and late luteal phases, and pre-ovulatory stage). The metabolomic profiling of EVs was performed by proton nuclear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 56 publications
3
24
0
1
Order By: Relevance
“…In the study from Alminana et al [10] and ours, frozen-thawed oEVs collected from oviductal fluids at the postovulatory stage were used. Furthermore, as previously reported [7], the proportions of exosomes (30-100 nm: 76%) and of microvesicles (100-500 nm: 24%), as measured by transmission electron microscopy in the oEV samples used, were very similar in the two studies. However, the differences between the two studies may be due to differences in oEV content in the culture media: based on preliminary (unpublished) data comparing different doses of oEVs proteins (0.005, 0.05, 0.5 mg/mL) in the culture medium, the 0.05 dose tended to increase the rates of blastocysts at days 7-8 compared to controls without oEVs and was chosen for the present study, whereas Alminana et al [10] used final concentrations of 0.2-0.4 mg of proteins/mL.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the study from Alminana et al [10] and ours, frozen-thawed oEVs collected from oviductal fluids at the postovulatory stage were used. Furthermore, as previously reported [7], the proportions of exosomes (30-100 nm: 76%) and of microvesicles (100-500 nm: 24%), as measured by transmission electron microscopy in the oEV samples used, were very similar in the two studies. However, the differences between the two studies may be due to differences in oEV content in the culture media: based on preliminary (unpublished) data comparing different doses of oEVs proteins (0.005, 0.05, 0.5 mg/mL) in the culture medium, the 0.05 dose tended to increase the rates of blastocysts at days 7-8 compared to controls without oEVs and was chosen for the present study, whereas Alminana et al [10] used final concentrations of 0.2-0.4 mg of proteins/mL.…”
Section: Discussionsupporting
confidence: 84%
“…The oEVs used were obtained from a pool of bovine oviductal fluids collected at a local commercial slaughterhouse and isolated by centrifugation (12,000× g, 15 min) and two successive ultracentrifugations (100,000× g, 90 min), then characterized by transmission electron microscopy and western blotting as detailed in our previous study [7]. Only oviducts at the postovulatory stage of cycle (recently formed corpus luteum, absence of follicles >10 mm; estimated Days 1-5 postovulation) and ipsilateral to ovulation, i.e., at the expected time and site of embryo development, were used.…”
Section: In Vitro Embryo Production and Oevs Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide range of oEV components recently identified in our laboratory (mRNAs, proteins, ncRNAs including miRNAs, snoRNAs, snRNAs, and metabolites) [19,20], it is difficult to select potential candidates as modulators of embryonic development. To date, only a few miRNAs and proteins have been proven to be responsible for oEVs' functional effects on spermatozoa [11,16], while the functional impact of the oEV cargo on embryos and the extent of those effects is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bridi et al summarize the current knowledge about the potential roles of both maternal (including oviduct and uterus) and embryonic EVs in the crucial events leading to successful pregnancy [ 7 ]. To increase the current knowledge of the oviductal EVs molecular cargo, Gatien et al focused on a less known cargo, characterizing metabolomic profile of bovine oviductal EVs during the estrous cycle [ 28 ]. Their study revealed up to 100-fold higher levels of glucose-1-phosphate and maltose at the luteal phase compared to the peri-ovulatory phases.…”
Section: The Extracellular Vesiclesmentioning
confidence: 99%